2022
DOI: 10.2147/ccid.s365682
|View full text |Cite
|
Sign up to set email alerts
|

UVR Promotes Keratinocyte Phagocytosis and Skin Pigmentation Through TRPA1 Channels

et al.

Abstract: Ultraviolet radiation (UVR) enhances skin pigmentation, which involves the production of melanin by melanocytes and subsequent transfer to keratinocytes. In the epidermis, keratinocyte phagocytosis plays a pivotal role in the process of melanosome transfer to protect DNA of epidermal cells against damage from UVR. Previous research suggested that transient receptor potential channels ankyrin 1 (TRPA1) was required for UVR-induced early melanin synthesis in melanocytes. Currently, there is no evidence that supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
(44 reference statements)
0
2
0
Order By: Relevance
“…Our study and other teams’ research showed that ultraviolet or blue light can drive the mobilization of calcium stored in melanocytes and fibroblasts through OPN3 21 , 26 . Further studies found that UVA led to the intracellular calcium via transient receptor potential channels ankyrin 1 and promoted the phosphorylation of CaMKII in HaCaT 36 . However, whether the calcium signaling pathway is involved in melanin cap formation is unknown.…”
Section: Resultsmentioning
confidence: 97%
“…Our study and other teams’ research showed that ultraviolet or blue light can drive the mobilization of calcium stored in melanocytes and fibroblasts through OPN3 21 , 26 . Further studies found that UVA led to the intracellular calcium via transient receptor potential channels ankyrin 1 and promoted the phosphorylation of CaMKII in HaCaT 36 . However, whether the calcium signaling pathway is involved in melanin cap formation is unknown.…”
Section: Resultsmentioning
confidence: 97%
“…The overexposure of normal skin to solar UVR may give rise to short-term reactions such as erythema and atypical pigmentation, and long-term responses increasing a risk factor of developing photoaging and skin disorders [ 20 ]. Chronological aging in human skin, like photoaging is a cumulative biological process, which leads to the evolutionary modification of structural and functional features [ 21 ].…”
Section: Discussionmentioning
confidence: 99%